The Impact of Transposable Elements in Genome Evolution and Genetic Instability and Their Implications in Various Diseases - Selvam Ayarpadikannan; Heui-Soo Kim (Genomics & Informatics)
Approximately 45% of the human genome is comprised of transposable elements (TEs). Results from the Human Genome Project have emphasized the biological importance of TEs. Many studies have revealed that TEs are not simply "junk" DNA, but rather, they play various roles in processes, including genome evolution, gene expression regulation, genetic instability, and cancer disposition. The effects of TE insertion in the genome varies from negligible to disease conditions. For the past two decades, many studies have shown that TEs are the causative factors of various genetic disorders and cancer. TEs are a subject of interest worldwide, not only in terms of their clinical aspects but also in basic research, such as evolutionary tracking. Although active TEs contribute to genetic instability and disease states, non-long terminal repeat transposons are well studied, and their roles in these processes have been confirmed. In this review, we will give an overview of the importance of TEs in studying genome evolution and genetic instability, and we suggest that further in-depth studies on the mechanisms related to these phenomena will be useful for both evolutionary tracking and clinical diagnostics.